2017
DOI: 10.3892/mmr.2017.7577
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the key genes and pathways of osteosarcoma with pulmonary metastasis using a gene expression microarray

Abstract: Osteosarcoma is a common and highly malignant tumour in children and teenagers that is characterized by drug resistance and high metastatic potential. Patients often develop pulmonary metastasis and have a low survival rate. However, the mechanistic basis for pulmonary metastasis remains unclear. To identify key gene and pathways associated with pulmonary metastasis of osteosarcoma, the authors downloaded the gene expression dataset GSE85537 and obtained the differentially expressed genes (DEGs) by analyzing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Additionally, more specific biological processes were described, for instance, fibroblast proliferation, osteoblast differentiation and development, and mesenchymal cell proliferation and transition. In accordance with our results, previous studies have identified similar biological processes related to OS, where the following are considered OS-associated terms: cell cycle regulation (mainly mediated by RB1 and TP53), osteoblast differentiation (mediated by RUNX2), DNA damage, stress response, epigenetic processes, mitosis, cell motility functions, and members involved in OS cell proliferation (weighting NFKB signaling, NFKBIE, and RELA members) [3,[35][36][37]. Taken together, these processes suggest that the consensus list is evidence of the genes associated with osteogenesis, cell differentiation, and transition to bone cell types.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, more specific biological processes were described, for instance, fibroblast proliferation, osteoblast differentiation and development, and mesenchymal cell proliferation and transition. In accordance with our results, previous studies have identified similar biological processes related to OS, where the following are considered OS-associated terms: cell cycle regulation (mainly mediated by RB1 and TP53), osteoblast differentiation (mediated by RUNX2), DNA damage, stress response, epigenetic processes, mitosis, cell motility functions, and members involved in OS cell proliferation (weighting NFKB signaling, NFKBIE, and RELA members) [3,[35][36][37]. Taken together, these processes suggest that the consensus list is evidence of the genes associated with osteogenesis, cell differentiation, and transition to bone cell types.…”
Section: Discussionsupporting
confidence: 92%
“…The protein digestion and absorption pathway is a key pathway in several human cancers. A study by Shi et al showed that this pathway might contribute to the pulmonary metastasis of osteosarcoma patients [24]. It might be involved in the up-regulation of differentially expressed genes in breast cancer [25], and it has already been associated with the down-regulated differentially expressed genes in pancreatic neuroendocrine tumors [26].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the constant development of high-throughput technologies and improvements in data analysis techniques, microarray techniques combined with bioinformatics analyses have been extensively applied to identify genetic alterations at the genome level of tumors, particularly in seeking the differentially expressed genes (DEGs). At present, Shi et al have analyzed the enrichment pathway and key genes of lung metastasis of osteosarcoma using a single microarray [8] . However, due to the inherent differences in experimental samples, detection platforms, and experimental methods, falsepositive rates in independent microarray analysis reduce the reliability of the results obtained.…”
Section: Introductionmentioning
confidence: 99%